The esterification of xanthophylls in Solanum lycopersicum (tomato) chromoplasts; the role of a non-specific acyltransferase. (November 2021) - Lewis, Esther R.; Nogueira, Marilise; Enfissi, Eugenia M.A.; Fraser, Paul D.
Abstract: The esterification of carotenoids has been associated with high-level accumulation, greater stability and potentially improved dietary bioavailability. Engineering the formation of ketocarotenoids into tomato fruit has resulted in the esterification of these non-endogenous metabolites. A genotype of tomato was created that contains; (i) the mutant pale yellow petal (pyp) 1-1 allele, which is responsible for the absence of carotenoid esters in tomato flowers and (ii) the heterologous enzymes for ketocarotenoid formation. Analysis of the resulting progeny showed altered quantitative and qualitative differences in esterified carotenoids. For example, in ripe fruit tissues, in the presence of the pyp mutant allele, non-endogenous ketocarotenoid esters were absent while their free forms accumulated. These data demonstrate the involvement of the PYP gene product in the esterification of diverse xanthophylls. Graphical abstract: Image 1 Highlights: Tomato lines producing ketocarotenoids in a mutant pyp allele background have been created. The PYP gene is involved in the esterification of diverse xanthophylls. New volatile molecules derived from non-endogenous ketocarotenoids have been determined.